Giada's feel good food - De Laurentiis, Giada (Clarkson Potter/Publishers, 2013)
Food Network's most beautiful star reveals her secrets for staying fit and feeling great in this practical book with 120 healthy recipes including nutritional information, and personal lifestyle and beauty tips.